Complete Cervical Avulsion with Intravaginal Misoprostol for Second Trimester Pregnancy Termination. (2nd August 2012) - Sajjan, G. R.; Patil, Neelamma; Kaur, Manpreet; Shirgur, Shobha; Nandi, Suvarna; Ashwini, V.
Abstract : Intravaginal misoprostol, a synthetic PGE1 analogue, has largely replaced all other techniques for pregnancy termination in II trimester, because of its successful results. Incidence of II trimester pregnancy termination has also increased in the present days, because of prenatal diagnosis of pregnancies with serious fetal abnormalities like cardiovascular and skeletal malformations. But there are serious and life threatening complications reported with the use of intravaginal misoprostol. Here we are reporting a case of complete avulsion of cervix from lower part of the uterus, with the use of intravaginal misoprostol, for II trimester termination of pregnancy. So, clinicians dealing with II trimester termination of pregnancy should be aware of such complications.